(3cJGH aj CUhd Gdabgs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3GdCUhd hCjGJ GdCMcGe heG LGA ajgG ef GdSfI heG GJab YdjgG ef GLeGY hHGdLedI cd eG Od YdjgG Ohf eG dG jNJUs
(3BNQgG (B:s
(3BNQgG(B: (3ef fMh bhdge eWQfG RHGdI aGdKYdHjI hEfeG jQjO Cf GdeWQ CUGHgeG ef Hjf GdCeGcf dCf hbhYg aj GdKYdHjI cGf ef HYO RHGdI hefg bhdgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs